Post-normal evaluation?. (July 2019) - Schwandt, Thomas A.
Evaluation evolves, responding to developments in the technical, social, and political environments in which it unfolds as well as influencing how those contexts are to be understood and assessed. Evaluation has typically been understood as a reliable means of providing some assurance in the appraisal of the value of social interventions, but has increasingly been seen as having to address a variety of uncertainties and risks not simply in those appraisals per se but in the design and management of the interventions as well. Some new ways of thinking and forms of evaluation practice linked to planning and decision making are emerging reflecting assumptions of unpredictability as well as incompleteness, instability, and a plurality of perspectives in value determination. This may signal the emergence of "post-normal evaluation." This article explores several key features of this development.